Mineralogy and PGE geochemistry of chromitites and peridotites of the sapat complex in the indus suture zone, northern Pakistan: implications for magmatic processes in the supra-subduction zone. Issue 10 (31st May 2023) - Ullah, Zaheen; Li, Huan; Khan, Asad; Faisal, Shah; Dilek, Yildirim; Förster, Michael W.; Farhan, Muhammad; Ashraf, Umar; Khattak, Salman Ahmed; Rehman, Gohar; Hussain, Syed Asim
ABSTRACT: The Sapat Complex in Northern Pakistan contains remnants of the northern Neo-Tethys Ocean, presently exposed along the Indus Suture Zone. The mantle peridotites of the Sapat Complex include harzburgites, dunites, and subordinate lherzolites. Harzburgites are the dominant peridotite variety over dunites. The dunites are hosted by harzburgites and occur exclusively as 'envelopes' surrounding chromitite pods. The podiform chromitites show disseminated, banded, and massive textures. Chromitites exhibit variable Cr# [Cr/(Cr + Al)] and Mg# [Mg/(Mg + Fe 2+ )], which range from 0.76 to 0.77, and from 0.64 to 0.66, respectively, while TiO2 contents are <0.2 wt.%. These features perhaps reflect crystallization of the chromian spinel from a boninitic magma. Similarly, chromian spinel in peridotites manifest a wide range of Cr# and Mg#, from 0.49 to 0.83 and 0.41 to 0.57, respectively, and are characterized by very low TiO2 values, averaging at 0.1 wt.%. Chromian spinel of chromitites and peridotites of the Sapat Complex have also very low Fe 3+ # (<0.01), which indicate their crystallization under low oxygen fugacities. The platinum group elements (PGE) distributions show high (Os + Ir + Ru)/(Rh + Pt + Pd), very low Pd/Ir values, and are defined by a prominently fractionated chondritic normalized PGE pattern, hence, this deposit is a typical example of an ophiolitic chromitite. The studied peridotites are highly depleted in PGE compared to chondritic values. The PdN /IrN values, averaging to 1.5 in dunites are unfractionated, while PGE spidergrams of harzburgites and lherzolites depict minor positive slopes, a minor positive Ru anomaly, and have average PdN /IrN values of 2.3 and 2.4, respectively. Furthermore, the harzburgites, dunites, and lherzolites display generally flat chondritic and primitive mantle normalized PGE patterns, and therefore, are nearly identical to highly depleted mantle peridotites. The mineralogical and PGE geochemical imprints of Sapat Complex chromitites and peridotites establish a strong affinity to supra-subduction zone ophiolites. Moreover, calculated parental melts of the chromitites and various geochemical discrimination diagrams elucidate that the chromitites were derived from boninitic magma produced by melting of depleted mantle peridotites in an oceanic arc, characterized by low oxygen fugacity, similar to a supra-subduction zone tectonic setting. This research highlights the use of mineralogy and geochemical compositions of chromitites and peridotites to reveal deep magmatic processes in a supra-subduction zone environment. Graphical Abstract: uf0001